Analysis of the Use of Pig Oil on Chili Plants in an Islamic Perspective - Talitha Widyadhana; Maheswara Rabbani (Jurnal Ilmiah Wahana Pendidikan, 2023)
In Islamic teachings, there is particular concern regarding the issue of food that is permissible (halal) or forbidden (haram) for a Muslim to eat. Food prohibited for consumption in Islam is pork, carrion, blood, and meat slaughtered by mentioning a name other than Allah. Of course, these prohibitions have many wisdom pearls with a specific purpose. In plants, fertilizers or other nutrients are needed for the growth and development of these plants. This study aims to analyze the resistance of chili plants to pig oil and its comparison with the use of compost. In addition, this study aims to determine the use of pig oil for the cayenne pepper plant and whether it is halal or haram to eat it. The research method used was a literature study, experiments, and interviews with three different sources. The study found that pig oil made chili plants fertile even during the rainy season. The crops are halal because the pig oil has been processed in the leaves and stems, and the pig oil does not stick to the chilies.